Hydrothermal Conversion of Waste Biomass from Greenhouses into Hydrochar for Energy, Soil Amendment, and Wastewater Treatment Applications - Abu-Taher Jamal-Uddin; Shakirudeen A. Salaudeen; Animesh Dutta; Richard G. Zytner (Energies, 2022)
Solid hydrochar (HC) produced by hydrothermal carbonization (HTC) of tomato plant biomass from a greenhouse (GH) was assessed for different inhouse applications, including fuel, seed germination, and leached GH nutrient feed (GNF) wastewater treatment. Completed experiments showed encouraging results. HC was revealed to be an efficient renewable fuel, having peat-like characteristics with high heating value of about 26.0 MJ/kg and very low clinker forming potential. This would allow the use of HC as fuel for GH heating as a substitute to costly natural gas, or it could be commercialized after pelletizing. Experiments with soil application showed substantial potential for the produced HC in better seed germination of tomato plants. Another benefit from use of the produced HC is as a soil additive, which would also contribute to environmental emission reduction. Results suggest that the generated HC can remove about 6–30% of nutrients from leached-GNF wastewater. This would be an essential treatment in the reduction of nutrients from leached water from GH operations, and thus could prevent/reduce eutrophication. The exhausted HC after treatment application could then be reused for soil remediation. Overall, the paper highlights the potential applications of hydrothermal treatment in valorization of low-valued GH TPB waste, resulting in a circular economy.